Efficacy of Ferula Caspica Dried Sap by Extracting its Essential Oil Against the Clinical Yeast Isolates of Candida Albicans - Iqubal, S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The aim of this experiment is to study the efficacy of Ferula caspica dried sap by extracting its essential oil against the clinical yeast isolates of Candida albicans, along with the comparison of standard antifungal chemical agents used in the therapy. This study also focused on a rapid gas chromatogram–mass spectrometric analysis for the phytochemical constituents of F. caspica dried sap essential oil extract to know exactly its content as many literature mentioned about its rich chemical contents contributing 4–20% of volatile oil, 20–25% latex gum, and the remaining 40–65% of the resin. Materials and Methods: The clinical sample from the patients was collected by employing the aseptic technique and was inoculated on a sterile Rose Bengal Agar plate by streak plate method and incubated at 37°C for 24–48 h to observe the yeast oval colonies. Results and Discussion: The interpretation of the observation and results for the F. caspica essential oil extract has shown the rejoicing study results regarding its efficacy as potential antifungal agents when compared to that of the standard synthetic chemical agents used against the clinical isolates of C. albicans. Conclusion: This study, thus, suggests that these types of natural essential oils can also be employed for the treatment of many infectious agents in the future as an alternative medicine.